Kinetic, Equilibrium and Thermodynamic Studies on the Adsorption of Eu(III) by Eggshell from Aqueous Solutions - F. Granados-Correa; M. Jiménez-Reyes (Adsorption Science & Technology, 2013)
Eu(III) adsorption by eggshell from aqueous solutions was studied as a function of contact time, initial metal ion concentration and temperature through batch experiments. Analysis and discussions of possible mechanisms are included in the light of a comparison of currently known equilibrium adsorption models, kinetic models and thermodynamic parameters in open specialized literature. The experimental data fit very well with the Langmuir–Freundlich isotherm and the pseudo-second-order kinetic models. For thermodynamic considerations in terms of adsorption, the thermodynamics parameters ΔH°, ΔS° and ΔG° were evaluated, and the results indicated that the Eu(III) adsorption on eggshell is an endothermic and spontaneous process. These results show that eggshell is an effective, low-cost and widely available adsorbent in the field of lanthanide removal from aqueous solutions.